Association of Metabolic Syndrome Parameters with TT3 and FT3/FT4 Ratio in Obese Turkish Population - ÜSTAY, ÖZLEM (MARY ANN LIEBERT, INC, 2012)
Background: Obesity and metabolic syndrome are major health problems worldwide, including Turkey. Recent studies have shown an association between thyroid function tests and metabolic syndrome parameters. In this study, we aimed to determine the frequency of metabolic syndrome in an obese Turkish population and the relationship between metabolic syndrome and thyroid functions. Materials and Method: We recruited 211 patients (187 females/24 males; mean age, 39.7 +/- 11.7 years) with body mass index (BMI) >30 kg/m(2) and no other hormonal pathology that could cause obesity. Anthropometric evaluation was followed by measurement of fasting blood glucose (FBG), insulin, total cholesterol, triglycerides, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), thyroid-stimulating hormone (TSH), total triiodothyronine (TT3), total thyroxine (TT4), free T3 (FT3), and free T4 (FT4). Metabolic syndrome was defined according to the 2005 revision of the National Cholesterol Education Program Adult Panel III (NCEP ATP III) criteria. Insulin resistance was calculated from homeostasis model assessment of insulin resistance (HOMA-IR) formula. The TSH cutoff value was set at 2.5mU/L. Results: Metabolic syndrome was diagnosed in 122 patients (58%). Metabolic syndrome positive patients had significantly higher FBG, triglycerides, FT4, systolic (SBP) and diastolic blood pressure (DBP), and statistically lower HDL-C and FT3/FT4 ratio than metabolic syndrome negative patients. TSH decreased with age and was not related with any metabolic syndrome parameters. The FT3/FT4 ratio negatively correlated with FBG, triglycerides, SBP, and DBP (P = 0.003, r = -38; P = 0.02, r = -0.28; P = 0.005, r = -0.35; and P = 0.007, r = -0.34, respectively); TT3 positively correlated with HOMA-IR (P = 0.006, r = 0.40), FBG (P = 0.009, r = 0.38), and waist circumference (P = 0.02, r = 0.34). Conclusion: Metabolic syndrome frequency was increased in our study population compared to the general population. Metabolic syndrome parameters (except HDL) correlated with TT3, FT4, and the FT3/FT4 ratio. FT4 levels were associated with obesity and metabolic syndrome independently of insulin resistance, whereas TT3 levels were associated with both insulin resistance and metabolic syndrome. This relationship can be explained by compensatory effects of TT3, and probably FT4, on energy expenditure and thermogenesis in obese people.
Keywords: HEALTHY EUTHYROID SUBJECTS; THYROID-STIMULATING HORMONE; DISEASE RISK-FACTORS; WAIST HEIGHT RATIO; INSULIN-RESISTANCE; USEFUL PREDICTOR; FREE-THYROXINE; WEIGHT-LOSS; WOMEN; TSH